2(x-3)+8x=-36

Simple and best practice solution for 2(x-3)+8x=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)+8x=-36 equation:


Simplifying
2(x + -3) + 8x = -36

Reorder the terms:
2(-3 + x) + 8x = -36
(-3 * 2 + x * 2) + 8x = -36
(-6 + 2x) + 8x = -36

Combine like terms: 2x + 8x = 10x
-6 + 10x = -36

Solving
-6 + 10x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 10x = -36 + 6

Combine like terms: -6 + 6 = 0
0 + 10x = -36 + 6
10x = -36 + 6

Combine like terms: -36 + 6 = -30
10x = -30

Divide each side by '10'.
x = -3

Simplifying
x = -3

See similar equations:

| x^2+7x+3=-7 | | X+4=5(4x-2) | | Y=-0.1(420)+1 | | 8(u+2)-4u=-24 | | X-9=-6+-5 | | -25=4(w-8)+3w | | Y=-0.1(600)+1 | | 9/2x=60 | | 34=8(y+5)-6y | | 0.2x+25=9 | | m^2-10m+10=14 | | [5n+9]+17=4 | | 4x+17=x-19 | | r^3+8=0 | | 7p^2=-6p+3 | | Y=-0.1(45)+1 | | 16a+8b= | | 2x^2-6x+9=340 | | Y=2+4.5x | | -3x^4+16x^3-27x^2=0 | | y=4.5x+2 | | Y=-22.5x-1 | | -c+11=2.4+x | | log(2x)+log(3x)=log(96) | | 9/5(191.8) | | 4y-20x=8 | | (3x-4z)(x-7z)= | | 108x+4=13+46x-2 | | 35=m^2-2m | | -2x^2+8x-7=0 | | (y-7)-y=6 | | 4(v-7)+2v=8 |

Equations solver categories